(Fernando Távora e) Álvaro Siza: para a hipótese de uma singular condição do Novo na arquitectura portuguesa - Nuno Miguel de Sousa Gomes (2012)
The work designed and built by Álvaro Siza has been widely studied and commonly linked with the modern movement which, in many ways, continues to mark part of the discussion in the field of theory and critic of architecture. This master dissertation seeks to carry out a systematic study of the thought of Álvaro Siza based on his published writings but also considering his built works, with reference to modern experience, singled in a wider context that includes also the portuguese architecture and also more the contribution of Fernando Távora, for the construction of an idea that, in the scope of this research, allows us a problematization of the condition of new in architecture as a confrontation between two opposing concepts, from which a critical contribution to the contemporary debate is proposed.